Brentuximab vedotin, an antibody–drug conjugate, in patients with CD30‐positive haematologic malignancies and hepatic or renal impairment - Zhao, Baiteng (Br J Clin Pharmacol, 2016)
AIMS: Brentuximab vedotin, an antibody–drug conjugate (ADC), selectively delivers the microtubule‐disrupting agent monomethyl auristatin E (MMAE) into CD30‐expressing cells. The pharmacokinetics of brentuximab vedotin have been characterized in patients with CD30‐positive haematologic malignancies. The primary objective of this phase 1 open label evaluation was to assess the pharmacokinetics of brentuximab vedotin in patients with hepatic or renal impairment. METHODS: Systemic exposures were evaluated following intravenous administration of 1.2 mg kg(–1) brentuximab vedotin in patients with CD30‐positive haematologic malignancies and hepatic (n = 7) or renal (n = 10) impairment and compared with those of unimpaired patients (n = 8) who received 1.2 mg kg(–1) brentuximab vedotin in another arm of the study. RESULTS: For any hepatic impairment, the ratios of geometric means (90% confidence interval) for AUC(0,∞) were 0.67 (0.48, 0.93) for ADC and 2.29 (1.27, 4.12) for MMAE. Mild or moderate renal impairment caused no apparent change in ADC or MMAE exposures. Severe renal impairment (creatinine clearance <30 ml min(–1); n = 3) decreased ADC exposures (0.71 [0.54, 0.94]) and increased MMAE exposures (1.90 [0.85, 4.21]). No consistent pattern of specific adverse events was evident, but analysis of the safety data was confounded by the patients' poor baseline conditions. Five patients died due to adverse events considered unrelated to brentuximab vedotin. All had substantial comorbidities and most had poor baseline performance status. CONCLUSIONS: Hepatic impairment and severe renal impairment may cause decreases in brentuximab vedotin ADC exposures and increases in MMAE exposures.